Follow Up Case on Breast Reconstruction with ADM - Stefan Andrei COMAN; Horia TOADER; Mihai MEHEDINTU-IONESCU (Modern Medicine)
Breast cancer is the most common type of cancer found in women after skin cancer. It is also the second cause of cancer death in women after lung cancer. The incidence of breast cancer has decreased in the last decade due to the discontinuation of hormone replacement therapy in postmenopausal women The majority of women with breast cancer are in an early stage at the moment of detection and are eligible for breast conservation therapy and receive some form of systemic or local adjuvant therapy like chemotherapy or radiotherapy depending on the histological type of the tumor. Acellular dermal matrices or ADM for short are processed dermis that can be used as an adjuvant to local flap reconstruction or as the primary material for reconstruction of the nipple. In this article we discuss the case of a 42 year old woman with breast carcinoma who underwent mastectomy and breast reconstruction with silicone gel implant and ADM and answered a set of questions created to optimize the patient journey from diagnosis to reconstruction and follow-up.